New Music and Institutional Critique - Grüny, Christian; Farnsworth, Brandon (Ästhetiken X.0 - Zeitgenössische Konturen ästhetischen Denkens, 2024)
While institutional critique has long been an important part of artistic practice and theoretical debate in the visual arts, it has long escaped attention in the field of music. This open access volume assembles for the first time an array of theoretical approaches and practical examples dealing with New Music's institutions, their critique, and their transformations. For scholars, leaders, and practitioners alike, it offers an important overview of current developments as well as theoretical reflections about New Music and its institutions today. In this way, it provides a major contribution to the debate about the present and future of contemporary music.